Multidisciplinary team decision-making in cancer and the absent patient: a qualitative study. Issue 7 (21st July 2016) - Hamilton, D W; Heaven, B; Thomson, R G; Wilson, J A; Exley, C
Abstract : Objective: To critically examine the process of multidisciplinary team (MDT) decision-making with a particular focus on patient involvement. Design: Ethnographic study using direct non-participant observation of 35 MDT meetings and 37 MDT clinics, informal interviews and formal, semistructured interviews with 20 patients and 9 MDT staff members. Setting: Three head and neck cancer centres in the north of England. Participants: Patients with a diagnosis of new or recurrent head and neck cancer and staff members who attend the head and neck cancer MDT. Results: Individual members of the MDT often have a clear view of which treatment they consider to be 'best' in any clinical situation. When disagreement occurs, the MDT has to manage how it presents this difference of opinion to the patient. First, this is because the MDT members recognise that the clinician selected to present the treatment choice to the patient may 'frame' their description of the treatment options to fit their own view of best. Second, many MDT members feel that any disagreement and difference of opinion in the MDT meeting should be concealed from the patient. This leads to much of the work of decision-making occurring in the MDT meeting, thus excluding the patient. MDT members seek to counteract this by introducing increasing amounts of information about the patient into the MDT meeting, thus creating an 'evidential patient'. Often, only highly selected or very limited information of this type can be available or known and it can easily be selectively reported in order to steer the discussion in a particular direction. Conclusions: The process of MDT decision-making presents significant barriers to effective patient involvement. If patients are to be effectively involved in cancer decision-making, the process of MDT decision-making needs substantial review.